Strój jako narzędzie propagowania mieszczańskiego habitusu – analiza artykułów Barbary Hoff w „Przekroju” - Załęska, Olga (Studia Etnologiczne i Antropologiczne, 2022)
Olga Załęska analyses the content of Barbara Hoff ’s articles in the “Fashion” column in the weekly “Przekrój” in the years 1954–1969. Załęska conducted her research by taking into account the cultural, social and political context of the Polish People’s Republic, and primarily focusing on its unofficial class structure. Załęska argues that Hoff ’s publications had a significant symbolic meaning as tools of class struggle and of opposition to the ruling political power. Thus, they corresponded with the attitude of he intelligentsia whom this weekly brought closer together (as in the case of Leopold Tyrmand). In the “Fashion” column we can detect elements of the bourgeois habitus, which Hoff propagated among readers representing various social classes. Załęska analyses class aspects of Barbara Hoff 's educational message. Later statements by Hoff and members of the intelligentsia revolving around “Przekrój” ascribe a subversive potential to fashion as a way to resist the socialist system. Załęska explores this thesis, its defense made plausible by the assumption that the “resistance against the ruling power” is understood as a struggle with that power’s aesthetic and cultural aspect.